Transition Metal-free Approaches to Biaryls - Piazzolla, Francesca; Colognese, Francesco; Temperini, Andrea (Current Organic Chemistry, 2018)
Biaryls are a key structural motif in compounds with various applications, ranging from pharmaceuticals to material science, including ligands for organic synthesis. Given the growing concern about the use of transition metals in organic synthesis in terms of reaction condition mildness, substituents tolerance, reagents costs and toxicity, and purification of the products from metal traces, several alternatives have been developed to overcome the limitations of metal-catalyzed biaryls synthesis. Herein, we review the transition metal-free approaches to biaryls, which can be divided into metal-free crosscoupling of aromatics and metal-free benzannulation of aryl-substituted chains, as both fields have shown an impressive growth in recent years.
Keywords: cross-coupling